Transformasi Digital Sistem Informasi Akuntansi: Tinjauan Literatur Cloud, AI, dan Big Data - Wa Ode Irma Sari; Nita Hasnita; Yuni Maimunah (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2026)
Digital transformation has significantly changed Accounting Information Systems (AIS) through the adoption of various digital technologies. This study aims to analyze the development of digital transformation in accounting information systems with a focus on cloud computing, artificial intelligence (AI), and big data during the 2020–2026 period. The study employed a systematic literature review (SLR) approach based on the PRISMA 2020 guidelines. Data were collected from relevant scientific articles and analyzed using descriptive content analysis to identify research trends, benefits, challenges, and future opportunities related to digital technologies in AIS. The findings indicate that cloud computing serves as the primary infrastructure for real-time financial information access and management; artificial intelligence improves efficiency through the automation of accounting processes, auditing, and fraud detection; while big data supports data-driven decision-making, risk management, and information quality enhancement. The review further reveals that the integration of these technologies enhances the effectiveness of accounting information systems, although challenges related to data security, privacy, data quality, algorithm transparency, and digital competencies remain significant. This study highlights that digital transformation plays a crucial role in improving the quality and effectiveness of accounting information systems in the digital era.